2022
DOI: 10.1177/24730114221116790
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Volume Impacts Outcomes Following Ankle Fracture Repair

Abstract: Background: The purpose of this study was to determine the impact of surgeon volume on outcomes following ankle fracture fixation. Methods: Over 7 years, 362 patients who met inclusion criteria (>18 years with rotational ankle fractures) were identified and treated by orthopaedic surgeons at several hospitals within an academic medical center and were retrospectively reviewed. Surgeons that completed less than 24 ankle fixations per year (<90th percentile) during the study period were classified as low-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Brodeur et al 21 found that in a large population of patients who underwent primary total hip arthroplasty, patients who received the intervention from a lower volume surgeon or at a lower volume hospital had higher rates of readmission, in‐hospital mortality, and revision among various other postoperative morbidities. Similar findings have been described for other orthopedic procedures including common spine, ankle, and shoulder surgeries 22–25 . Therefore, the aim of this study is to evaluate the extent of healthcare segregation for AIAN patients receiving common orthopedic arthroplasty and trauma surgeries.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Brodeur et al 21 found that in a large population of patients who underwent primary total hip arthroplasty, patients who received the intervention from a lower volume surgeon or at a lower volume hospital had higher rates of readmission, in‐hospital mortality, and revision among various other postoperative morbidities. Similar findings have been described for other orthopedic procedures including common spine, ankle, and shoulder surgeries 22–25 . Therefore, the aim of this study is to evaluate the extent of healthcare segregation for AIAN patients receiving common orthopedic arthroplasty and trauma surgeries.…”
Section: Introductionsupporting
confidence: 64%
“…Similar findings have been described for other orthopedic procedures including common spine, ankle, and shoulder surgeries. [22][23][24][25] Therefore, the aim of this study is to evaluate the extent of healthcare segregation for AIAN patients receiving common orthopedic arthroplasty and trauma surgeries. We hypothesized that AIAN patients would be more likely to receive care from a lower volume surgeon and/or at a lower volume hospital compared to White patients.…”
mentioning
confidence: 99%
“…The results of all wound cultures were positive in 552 patients (55.9%). The positivity rates were 48.7% and 70.0% for grades II and III open fractures, respectively ( Most pathogens, except Pseudomonas aeruginosa, Enterobacter cloacae, and Acinetobacter baumannii, were sensitive to the prophylactic antibiotics according to the EAST guidelines [5]. We found Gram-negative strains in 83 (30.5%) of grade II open fractures and 84 (30.2%) of grade III open fractures.…”
Section: Resultsmentioning
confidence: 76%
“…Infections and complications remain major obstacles to the treatment of open fractures of the lower extremities [5][6][7][8]. Our multicenter study was a retrospective study based on six trauma centers in East China, including the Shanghai Jiao Tong University affiliated Sixth People's Hospital (Shanghai, China), the Xiamen University affiliated Fuzhou Second Hospital (Fuzhou, China), the first affiliated hospital of Soochow University (Suzhou, China), the Tongde Hospital of Zhejiang Province (Hangzhou, China), the Second Hospital of Anhui Medical University (Hefei, China), and Shandong Provincial Hospital (Jinan, China).…”
Section: Discussionmentioning
confidence: 99%